Analysis of Fluoride Contamination in Sheep Serum and in Water in the North East of Tunisia Ore Deposits - Hadiji, Rim; Bannouri, Iheb; Zelfani, Saida; Mamlouk, Aymen; Jaballah, Hela; Jemmal, Arij; Sdouga, Nadia; Ben Youssef, Samir (Frontiers in Toxicology, 2021)
The north east of Tunisia ore deposits (Hammam Zriba) contain a large amount of fluorites constituting a risk of environmental pollution as well as risks to human and animal health. The aim of our work was to assess the levels of fluorides in the water and blood of sheep in the east of Tunisia region This analysis study included 78 water samples and 60 blood samples taken during 3 days in the year 2019, from a sheep herd at Hammam Zriba delegation. The determination of fluorine concentration in the samples was carried out by potentiometry with a selective electrode type ISE combined Fluoride perfectION™. High Fluoride concentrations were found at a mean of 1.62 ± 1.18 ppm, 1.45 ± 0.98 ppm and 2.65 ± 1.61 ppm, respectively in running, deep and stagnant waters. In addition, 83.3% of the animals reared within 400 meters of the study area had elevated fluoride levels in the blood exceeding the usual values (fluoremia> 0.15ppm). The concentration of fluoride in the blood of the animals decreases with increasing distance from the mine.